Research Writing Competence of Grade 12 Students: Towards Research Culture Improvement - Cuayzon, Mark Lester (Journal of Interdisciplinary Perspectives, 2024)
This study examined the research writing competence of Grade 12 students using a descriptive-correlational design. The sample comprised 315 students from various academic tracks, assessed with a validated teacher-made survey questionnaire. Results indicated a moderately high level of research writing competence overall, with the STEM strand showing the highest proficiency. Significant differences in research competence among academic tracks were noted, reflecting the influence of diverse instructional methods and socio-economic factors. A positive correlation between academic grades and research competence was found, suggesting that students with higher academic performance generally possessed better research writing skills. Recommendations to enhance research writing competence included improving instructional qu This study examined the research writing competence of Grade 12 students using a descriptive-correlational design. The sample comprised 315 students from various academic tracks, assessed with a validated teacher-made survey questionnaire. Results indicated a moderately high level of research writing competence overall, with the STEM strand showing the highest proficiency. Significant differences in research competence among academic tracks were noted, reflecting the influence of diverse instructional methods and socio-economic factors. A positive correlation between academic grades and research competence was found, suggesting that students with higher academic performance generally possessed better research writing skills. Recommendations to enhance research writing competence included improving instructional quality, promoting collaborative research projects, providing regular practice and feedback, establishing mentorship programs, integrating research skills throughout the curriculum, fostering a research culture, and involving parents and the community. These strategies aim to improve students' research writing skills and academic performance, preparing them for future educational and professional challenges. ality, promoting collaborative research projects, providing regular practice and feedback, establishing mentorship programs, integrating research skills throughout the curriculum, fostering a research culture, and involving parents and the community. These strategies aim to improve students' research writing skills and academic performance, preparing them for future educational and professional challenges.